MANAGEMENT OF PERI-IMPLANTITIS IN PERI-IMPLANT THERAPY - Zugravu Cosmin; Butnariu (Constantinescu); Cretu Cosmin; Tibeica Andreea; Curca Razvan; Tibeica Silviu Catalin; Agop-Forna Doriana; Norina Forna (Romanian Dental Association for Education, 2023)
Although dental implants have a high success rate, peri-implantitis is the most common complication in dental implantology. This article discusses various factors associated with peri-implantitis, prevalence and different available treatments, highlighting their advantages and disadvantages.[1]In a high percentage, failure is due to local infection, which occurs through bacterial proliferation, represented by fungi and biofilm formation, of peri-implant origin.In a greater proportion of the peri-implantitis samples, a diversity of bacterial species was found, these being: Porphiromonas gingivalis, Treponema denticola and Tannerella forsythia[2]. The main risk indicators of peri-implant diseases are: plaque, smoking, history of periodontitis, surface roughness, residual cement, appearance angle > 30 degrees, radiotherapy, keratinized tissue width and implant operating time, gender and diabetes. Peri-implantitis treatments can be divided into non-surgical (mechanical, antiseptic and antibiotic), surface decontamination (chemical and laser), and surgical (abrasive, resective and regenerative air powder). To ensure the success of the treatment, mechanical debridement must always be combined with other treatments (antiseptic and surgical treatment)[1]